Eagle syndrome causing cerebral sinus hypertension: Case report - Erik Werheim, BS; Zachary Sokol, MA; David Brown, MD; Martin Oselkin, MD (Radiology Case Reports, 2023)
Eagle Syndrome is a rare condition with a variety of presentations, resulting from an enlarged styloid process or calcified stylohyoid ligament. Due to the variety of presentations, diagnosis can be difficult. In this report, we present a case of ES that presented with a constellation of neurological symptoms, including headache and visual disturbance, ultimately found to be due to cerebral sinus hypertension, exacerbated by certain movements, caused by an enlarged styloid process with calcification of the stylohyoid ligament, consistent with ES. The patient underwent styloidectomy with immediate resolution of symptoms. This case report illustrates the diagnostic quandary often posed by ES and hopes to add further understanding to its presentation and diagnosis.